Climate change - a challenge and an opportunity for law and justice - Tiedeken, Tjarda (Vilnius University Open Series, 2023)
The article “Der Klimawandel als Chance für die Beziehung zwischen Recht und Gerechtigkeit” aims to further the discussion on a possible justification of environmental activism (particularly in the German legal system). The author, Tjarda Tiedeken, finds that actions of climate change activists may fall under the definition of civil disobedience. She states that due to the superiority over ‘common’ crime and the relative effect of majority decisions, civil disobedience aiming to prevent state decisions with irreversible consequences must be justified. The author discusses the ‘irreversibility criterion’ as part of this justification, yet she finds it to lack differentiation causing a lack of practicability. Despite the unsuitability of the criterion examined, the author concludes that anyone who stands up against climate change for the preservation of democracy and even of humanity itself, cannot be treated like a person who transgresses the law out of pure self-interest. How a justification could be designed instead remains subject of further discussion, to which the author attempts to find an answer in her dissertation.